2017
DOI: 10.1093/nar/gkx896
|View full text |Cite
|
Sign up to set email alerts
|

Loss of imprinting mutations define both distinct and overlapping roles for misexpression of IGF2 and of H19 lncRNA

Abstract: Imprinted genes occur in discrete clusters that are coordinately regulated by shared DNA elements called Imprinting Control Regions. H19 and Igf2 are linked imprinted genes that play critical roles in development. Loss of imprinting (LOI) at the IGF2/H19 locus on the maternal chromosome is associated with the developmental disorder Beckwith Wiedemann Syndrome (BWS) and with several cancers. Here we use comprehensive genetic and genomic analyses to follow muscle development in a mouse model of BWS to dissect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…Among several regulators of mTOR signaling that have been exported, we first suggest that the expression of lncRNA H19 is remarkably upregulated by IL-22 in hepatocytes and that the IL-22-STAT3-lncRNA H19 signaling pathway is significant for the activation of mTOR and the preservation of mitochondrial fitness during hepatocyte damage. In agreement with previous studies, we show that lncRNA H19 affects the upstream regulators of mTOR signaling, such as AMPK, AKT proteins, thereby activates mTOR and induces the expression of a subset of metabolic reprogramming regulators in hepatocytes [30,[44][45][46]. Accordingly, we find that lncRNA H19 plays a central role in the inhibition of mitochondrial ROS accumulation and dysfunctional mitochondria elimination in hepatocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Among several regulators of mTOR signaling that have been exported, we first suggest that the expression of lncRNA H19 is remarkably upregulated by IL-22 in hepatocytes and that the IL-22-STAT3-lncRNA H19 signaling pathway is significant for the activation of mTOR and the preservation of mitochondrial fitness during hepatocyte damage. In agreement with previous studies, we show that lncRNA H19 affects the upstream regulators of mTOR signaling, such as AMPK, AKT proteins, thereby activates mTOR and induces the expression of a subset of metabolic reprogramming regulators in hepatocytes [30,[44][45][46]. Accordingly, we find that lncRNA H19 plays a central role in the inhibition of mitochondrial ROS accumulation and dysfunctional mitochondria elimination in hepatocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, understanding the underlying mechanisms of myogenesis is particularly important. Although thousands of lncRNAs have been identified [38,50], a minority of functional lncRNAs, such as TncRNA [51], lncMD [52], H19 [52][53][54][55][56], and lncIRS1 [57], are involved in mammal myogenesis. MEG3, a differentially expressed lncRNA during postnatal skeletal muscle development in pigs, has four crucial polymorphism sites associated with back fat thickness [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the H19/ IGF2 locus, both genes share a common set of enhancers, which are located downstream of the H19 gene [18]. Differentially methylated regions in these two genes have also been implicated in a range of biological processes and diseases, largely because of their role regulating composition of the body [39][40][41][42]; however, little research has been carried out in terms of PCOS in this respect. One previous study showed that IGF2 is a host gene of miR-483-5p and recorded significantly lower levels of IGF2 in the cumulus cells of women with PCOS [43].…”
Section: Discussionmentioning
confidence: 99%